Normative regulation of water objects safety - Pastukhov Сергей Михайлович; Osmanov Хикмет Сабирович; Mikanovich Дмитрий Станиславович (Journal of Civil Protection, 2021)
Purpose. To analyze the normative regulation of the safety of hydraulic structures (reservoirs, sludge storage facilities, reservoirs for technical purposes) in the countries of Central Asia in order to determine the legal framework for organizing their safe operation. To substantiate the main directions of improving the system of ensuring safety and reliability of hydraulic structures of the pressure front. Methods. The method of theoretical analysis of references was applied in assessing the regulatory and legal framework of the Central Asian countries in the field of ensuring safety of hydraulic structures of various types. The processing of the obtained results is carried out using the method of estimation and theoretical generalization of the data obtained. Findings. It has been established that the regulation of relations in the field of safe operation of hydro-technical structures in the countries of Central Asia is carried out on the basis of general legislation on water management, energy and ecology. These legislative acts define the legal framework for organizing the safe operation of various types of hydraulic structures, however, there are no mechanisms (methods) to assess the risk of emergencies at the structures of the pressure front (reservoirs, sludge storage facilities, technical reservoirs) taking into account all the features (locations, methods of regulation, granulometric composition of soils, chemical composition of the filtering fluid). Thus, an urgent task is to develop a methodology for assessing the risk of hydrodynamic accidents at the pressure front structures, taking into account their distinctive features. Application field of research. The research results can be used for a comprehensive assessment of the state of hydraulic structures by the Ministry of Natural Resources, as well as the Ministry of Emergency Situations in the development of medium and long-term forecasts of emergencies.